Analysis of Competitiveness and Factors Affecting Indonesian Coal Exports - Oka, I Gusti Ayu Michelle Audi Natasha; Karmini, Ni Luh (CV. Rayyan Dwi Bharata, 2025)
Indonesia is one of the largest countries that play a role in world coal exports. Coal is one of the non-oil and gas or mining export commodities that has an important role in the economy. The purpose of this study is to analyze the competitiveness and factors that influence Indonesia’s coal exports to the five main destination countries in 2012-2022. The data used is panel data, which is a combination of time series and cross-section data obtained through the Central Bureau of Statistics, BP Statistical Review Of World Energy, UN Comtrade, World Bank, as well as related articles and journals. To analyze the comparative competitiveness of Indonesian coal commodities in the five destination countries, the RCA (Revealed Comparative Advantage) method is used. This study uses a non-participant observation data collection method. The data analysis technique in this study is panel data regression analysis using Eviews 12 software. The results of this study indicate that the competitiveness and economic distance variables have a positive and significant effect on the volume of Indonesia’s coal exports to the five destination countries, while the exchange rate and GDP variables have a negative and insignificant effect on Indonesia’s coal exports to the five destination countries.